Evaluation of agricultural byproducts for the production of betaglucosidase by Aspergillus niger MBT-2 using solid state fermentation (Bangladesh Journal of Botany, 2020)
The experiment was conducted to isolate and screen fungal strain and optimization of solid-state fermentation conditions for enhanced production of β-glucosidase. Different fungal cultures were isolated and screened for β-glucosidase production. The physicochemical and nutritional parameters were optimized for enhanced production of β-glucosidase from higher producer. Among all the isolates the isolate which exhibited highest β-glucosidase potential was identified and assigned the code as Aspergillus niger MBT-2. The optimum β-glucosidase production was obtained in M5 medium containing wheat bran after 72 hrs of incubation at 40°C, pH 6 and 20 ml of moisture contents. In addition to this 2% fructose and 2% yeast extract proved to be best carbon and nitrogen sources, respectively and gave maximal enzyme productivity. The exploitation of agricultural by products as a substrate reduced the production cost of enzyme and makes the process economical. The Aspergillus niger MBT-2 has promising potential of bioconversion of low-cost material into valuable product like β-glucosidase.